THREE-DIMENSIONAL ANALYSIS OF NORMAL FAULT ZONES IN KARDIA MINE, PTOLEMAIS BASIN, NW GREECE - Delogkos, E.; Manzocchi, T; Childs, C.; Sachanidis, C.; Barmpas, T.; Chatzipetros, A.; Walsh, J. J.; Pavlides, S. (Bulletin of the Geological Society of Greece, 2016)
Six normal fault zones, with throws ranging from a few meters up to 50 m, were studied within an active, open pit, lignite mine in Ptolemais. Each fault was mapped 20 times over a period of five years because at intervals of ca. 3 months working faces are taken back between 20 and 50 m exposing fresh fault outcrops for mapping. Various resolutions of photographs and structural measurements were imported into a fully georeferenced 3D structural interpretation package, resulting in aseismic scale and outcrop resolution 3D fault volume with outcrop and panoramic photographs acting as the seismic sections in equivalent seismic surveys. Low resolution 3D models for the fault system structure at mine scale and higher-resolution 3D models for the fault zone structure were produced after geological interpretation and they can be used for qualitative and quantitative analysis.